Sistem Informasi Kesatuan Pengelolaan Hutan Yogyakarta Berbasis Web - Hidayat, Rochmad; Pratomo, Dinar Nugroho; Santoso, Probo; Oktalina, Silvi Nur (Politeknik Harapan Bersama, 2025)
The Forest Management Unit Information System (SIKPH) is a platform that integrates information technology to improve the efficiency and effectiveness of forest management. This research aims to develop a web-based SIKPH as a modern solution for the Forest Management Unit in Yogyakarta. The system development method uses the scrum methodology, which consists of requirements analysis, system design, implementation, and evaluation. Requirements analysis was conducted by understanding the demands and challenges faced by the Yogyakarta Forest Management Unit. Based on this analysis, the system design includes web architecture, user interface, database, and functionality that supports forest management processes. System implementation using the Laravel framework with performance testing shows an average response time of 1.2 seconds for 20 simultaneous users and 2.0 seconds for 30 users. User acceptance evaluation involved 30 respondents with beta testing results showing an average satisfaction level of 4.4 out of 5 for aspects of ease of use (4.3), feature compatibility (4.5), and system benefits (4.6). The system includes modules for forest sustainability monitoring, inventory management, and reporting with a 96% implementation success rate based on functional testing. The results of this research provide a positive contribution to forest management in Yogyakarta by improving process efficiency by 40% compared to the previous manual system.